Unpleasant symptoms of immunotherapy for people with lung cancer: A mixed-method study. (March 2023) - Zhang, Jingyu; Wang, Sichao; Zhou, Zihao; Lei, Cheng; Yu, Hongfan; Zeng, Cheng; Xia, Xin; Qiao, Guibing; Shi, Qiuling
Abstract: Background: Immunotherapy has changed the outlook for lung cancer treatment. A closer look at the accompanying symptoms from the patient's perspective is necessary to improve their tolerance to the treatment, which is also the basis for standardized symptom management. Objective: To describe the symptomatic experiences of patients receiving immunotherapy for lung cancer and explore whether symptoms reported during immunotherapy were associated with survival outcomes. Design: Exploratory sequential mixed-method study. Settings: Patients were continuously recruited from the oncology day ward of Guangdong Provincial People's Hospital between October 2019 and January 2020. Participants: 59 patients with advanced lung cancer and receiving immunotherapy (median [IQR] age was 64 [58–69]; 72.9 % pathological stage was IV) were included in the study. Methods: A sequential qualitative interview on symptom experiences was conducted from the perspective of lung cancer patients in immunotherapy. Summative content analysis was used to develop a standardized symptom reporting checklist. Survival outcome follow-ups of each patient were conducted 2 years after the interview. Results: 47 symptoms were extracted from the 124 interviews of 59 patients, the common symptoms including musculoskeletal pain (52.5 %), itchy skin (45.8 %), fatigue (45.8 %), cough (44.1 %), shortness of breath (32.2 %), lack of appetite (32.2 %), and rashes (32.2 %). The timing, severity, and interference of symptoms were different among patients. The symptoms of shortness of breath, fatigue and chest pain were more common in chemo-immunotherapy, while dry mouth and blurred vision were more frequent with immunotherapy. The symptoms of musculoskeletal pain, shortness of breath, lack of appetite, drowsiness and taste change were more common for those who died two years after the interviews; for those who survived, the symptoms of rash and chill were more common. Conclusions: We generated a symptom list related to lung cancer immunotherapy from the patients, provided a closer look at symptoms from the patient's perspective, and suggested differences in the presence of symptoms between the group of treatment and survival outcome. This enables clinicians and nurses to better understand and empathize with the patient's experience, so as to truly practice the essence of patient-centered care, and provide a basis for the development of standardized symptom measurement tools in the future. Tweetable abstract: At least 47 unpleasant symptoms were present in immunotherapy from the perspective of lung cancer patients.